Microglial crosstalk with astrocytes and immune cells in amyotrophic lateral sclerosis - Calafatti, Matteo; Cocozza, Germana; Limatola, Cristina; Garofalo, Stefano (Frontiers in Immunology, 2023)
In recent years, biomedical research efforts aimed to unravel the mechanisms involved in motor neuron death that occurs in amyotrophic lateral sclerosis (ALS). While the main causes of disease progression were first sought in the motor neurons, more recent studies highlight the gliocentric theory demonstrating the pivotal role of microglia and astrocyte, but also of infiltrating immune cells, in the pathological processes that take place in the central nervous system microenvironment. From this point of view, microglia-astrocytes-lymphocytes crosstalk is fundamental to shape the microenvironment toward a pro-inflammatory one, enhancing neuronal damage. In this review, we dissect the current state-of-the-art knowledge of the microglial dialogue with other cell populations as one of the principal hallmarks of ALS progression. Particularly, we deeply investigate the microglia crosstalk with astrocytes and immune cells reporting in vitro and in vivo studies related to ALS mouse models and human patients. At last, we highlight the current experimental therapeutic approaches that aim to modulate microglial phenotype to revert the microenvironment, thus counteracting ALS progression.